FOXP3 mutations causing early‐onset insulin‐requiring diabetes but without other features of immune dysregulation, polyendocrinopathy, enteropathy, X‐linked syndrome. Issue 3 (29th November 2017) - Hwang, Jessica L; Park, Soo‐Young; Ye, Honggang; Sanyoura, May; Pastore, Ashley N; Carmody, David; del Gaudio, Daniela; Wilson, Janna F; Hanis, Craig L; Liu, Xiaoming; Atzmon, Gil; Glaser, Benjamin; et al.
Abstract : Diabetes occurs in 1/90 000 to 1/160 000 births and when diagnosed under 6 months of age is very likely to have a primary genetic cause. FOXP3 encodes a transcription factor critical for T regulatory cell function and mutations are known to cause "immune dysregulation, polyendocrinopathy (including insulin‐requiring diabetes), enteropathy, X‐linked" (IPEX) syndrome. This condition is often fatal unless patients receive a bone‐marrow transplant. Here we describe the phenotype of male neonates and infants who had insulin‐requiring diabetes without other features of IPEX syndrome and were found to have mutations in FOXP3 . Whole‐exome or next generation sequencing of genes of interest was carried out in subjects with isolated neonatal diabetes without a known genetic cause. RT‐PCR was carried out to investigate the effects on RNA splicing of a novel intronic splice‐site variant. Four male subjects were found to have FOXP3 variants in the hemizygous state: p.Arg114Trp, p.Arg347His, p.Lys393Met, and c.1044+5G>A which was detected in 2 unrelated probands and in a brother diagnosed with diabetes at 2.1 years of age. Of these, p.Arg114Trp is likely a benign rare variant found in individuals of Ashkenazi Jewish ancestry and p.Arg347His has been previously described in patients with classic IPEX syndrome. The p.Lys393Met and c.1044+5G>A variants are novel to this study. RT‐PCR studies of the c.1044+5G>A splice variant confirmed it affected RNA splicing by generating both a wild type and truncated transcript. We conclude that FOXP3 mutations can cause early‐onset insulin‐requiring diabetes with or without other features of IPEX syndrome.